Femtosecond laser produced periodic plasma in a colloidal crystal probed by XFEL radiation; Scientific Reports; Vol. 10 - Mukharamova N. Nastasia; Lazarev S. V. Sergey Vladimirovich; Meijer J. M. Janne Mieke; Gorobtsov O. Yu. Oleg; Singer A. Andrej (2020, 2020)
Title screen